The Soviet Union position on the Kurdish Issue 1970 - 1974 In the light of Al Takhi Newspaper - Mirkhan, Hozan S. (Humanities Journal of University of Zakho, 2016)
This study deals with the Soviet Union position on the Kurdish issue (1970 – 1974) in the light of Al Takhi Newspaper, the mouthpiece of the Kurdish Democratic Party and the Kurdish movement at that time. The Soviet position on the Kurdish issue, during the period of the research, is one of the important topics addressed by Al Takhi newspaper. It has followed the developments in the Soviet position on the Kurdish issue, and published many articles expressing its opinion on that. Al Takhi Newspaper has revealed some ambiguities in these issues such as the convergence between Iraq and the Soviet Union, the Soviet position on the improvement of relations between the Iraqi government and the leadership of Kurdish movement, which resulted in statement of 11 March, 1970 agreement, as well as the Treaty of friendship between the Iraqi government and the Soviet Union in 1972, which eventually led to the deterioration of relations between the Kurds and the Iraqi Communist party.